2020
DOI: 10.1016/j.ejro.2020.100227
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-wire deployment techniques of option elite inferior vena cava filter: 3D printing vena cava phantom study

Abstract: To compare filter tilt and filter jumping during Option inferior vena cava (IVC) filter deployment with 3 different wires techniques using a 3-dimensional (3D) printing vena cava phantom. Materials and methods: An IVC 3D printed vena cava phantom was made from a healthy young male's computed tomographic data. Option IVC filters were deployed with 3 different wires: i) original push wire, ii) hydrophilic stiff wire, and iii) bent stiff wire. Right internal jugular and right femoral access were used 5 times with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
1
1
Order By: Relevance
“…In addition, the original guide wire had the lowest filter tilt ratio (0.34 vs. 0.57 and 0.58 for stiff hydrophilic wire and bent stiff wire, respectively, p ¼ 0.045) in the jugular access approach. 25 Note the filter tilt ratio was more significant in this study in comparison to the study of Kim et al, 5 which could be secondary to the elasticity of the phantom model and the lack of physiologic variables such as respiratory motion and cardiac cycles. In our practice, we believe that the OTW technique can improve the filter stability and reduce the filter tilt, particularly in a tortuous IVC.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, the original guide wire had the lowest filter tilt ratio (0.34 vs. 0.57 and 0.58 for stiff hydrophilic wire and bent stiff wire, respectively, p ¼ 0.045) in the jugular access approach. 25 Note the filter tilt ratio was more significant in this study in comparison to the study of Kim et al, 5 which could be secondary to the elasticity of the phantom model and the lack of physiologic variables such as respiratory motion and cardiac cycles. In our practice, we believe that the OTW technique can improve the filter stability and reduce the filter tilt, particularly in a tortuous IVC.…”
Section: Discussioncontrasting
confidence: 51%
“…Conjunctive endovascular strategies could also be a factor for potential IVC filter tilt. 14 Park et al 15 demonstrated that implementing the original push wire technique through FVs approach led to a significantly increased incidence of IVC filter tilt. In contrast, employing a bent stiff wire via IJV access resulted in a higher prevalence of filter tilt.…”
Section: Discussionmentioning
confidence: 99%